Pemberdayaan Masyarakat Dalam Beternak Lebah Madu Trigona SP. Dan Pupuk Organik Berbasis Mikroorganisme Untuk Menekan Perusakan Hutan Di Desa Tukadaya, Kecamatan Melaya, Kabupaten Jembrana-Bali - I Wayan Widana (Universitas Muhammadiyah Mataram, 2025)
The Kosabangsa program aims to reduce forest destruction by the community through community empowerment. The methods used include socialization, training and mentoring, monitoring and evaluation, and program sustainability. The focus of the activity is 2, namely raising Trigona sp. honey bees and utilizing livestock waste into organic fertilizer to reduce forest destruction in Tukadaya Village, Melaya District, Jembrana Regency, Bali. Partners hope that there will be an empowerment program to increase community knowledge and skills in raising Trigona sp. honey bees and making organic fertilizer. After the training and mentoring ends, the community has an understanding and skills in raising Trigona honey bees and organic fertilizer to increase income, so that forest destruction can be reduced and forest sustainability is maintained.